Retinal Layers Changes in Human Preclinical and Early Clinical Diabetic Retinopathy Support Early Retinal Neuronal and Müller Cells Alterations - Stela Vujosevic; Edoardo Midena (Journal of Diabetes Research)
Purpose. To evaluate the changes in thickness of individual inner and outer macular and peripapillary retinal layers in diabetes. Methods. 124 subjects (124 eyes) were enrolled: 74 diabetics and 50 controls. Macular edema, proliferative diabetic retinopathy (DR), any intraocular treatment and refractive error >6 diopters were the main exclusion criteria. Full ophthalmic examination, stereoscopic fundus photography, and spectral domain-OCT were performed. After automatic retinal segmentation (layering) in 5 layers, the thickness of each layer was calculated, and values compared among groups. Results. Thirty patients had no DR, 44 patients had non proliferative DR. A significant increase of inner plexiform and nuclear layers was found in DR eyes versus controls (P<0.001). A significant decrease (P<0.01) of retinal nerve fiber layer (RNFL) and at specific sites of retinal ganglion cell layer (P=0.02) was documented in the macula. In the peripapillary area there were no differences between diabetics and controls. Conclusions. Decreased RNFL thickness and increased INL/OPL thickness in diabetics without DR or with initial DR suggest early alterations in the inner retina. On the contrary, the outer retina seems not to be affected at early stages of DM. Automatic intraretinal layering by SD-OCT may be a useful tool to diagnose and monitor early intraretinal changes in DR.